Aquaporins as potential drug targets - Wang Fang; Feng Xue-chao; Li Yong-ming; Yang Hong; Ma Tong-hui (Acta Pharmacologica Sinica, 2016)
The aquaporins (AQP) are a family of integral membrane proteins that selectively transport water and, in some cases, small neutral solutes such as glycerol and urea. Thirteen mammalian AQP have been molecularly identified and localized to various epithelial, endothelial and other tissues. Phenotype studies of transgenic mouse models of AQP knockout, mutation, and in some cases humans with AQP mutations have demonstrated essential roles for AQP in mammalian physiology and pathophysiology, including urinary concentrating function, exocrine glandular fluid secretion, brain edema formation, regulation of intracranial and intraocular pressure, skin hydration, fat metabolism, tumor angiogenesis and cell migration. These studies suggest that AQP may be potential drug targets for not only new diuretic reagents for various forms of pathological water retention, but also targets for novel therapy of brain edema, inflammatory disease, glaucoma, obesity, and cancer. However, potent AQP modulators for in vivo application remain to be discovered.